Повышение качества изделий электронной техники путем моделирования стадий их производства - Shestakova, T. V. (PE "Politekhperiodika", Book and Journal Publishers, 2007)
A methodology for studying the technological process of integrated circuit production is considered with the aim of improving the quality of finished products under manufacturing conditions. An effective method is proposed for determining mathematical models that describe the dependence of output quality parameters on technological factors, based on measurements taken directly during the production process (using passive information).